Mengawali Rekonsiliasi Secara Menyeluruh Dalam Kasus Kekerasan Dalam Rumah Tangga (KDRT) - Iswanda Alfilia Prong; Hendry Corneles Mamengko Runtuwene (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2025)
Domestic violence, especially that experienced by children from an early age, leaves serious and lasting psychological, emotional, and spiritual impacts. This article discusses how the process of forgiveness and reconciliation can be a means of healing for victims of domestic violence, without neglecting justice and proper protection. The primary approach uses a psychospiritual perspective based on the REACH Forgiveness model developed by Everett L. Worthington Jr. Through forgiveness, victims are encouraged to free themselves from the shackles of revenge and emotional wounds. Reconciliation is understood not as an obligation to return to the perpetrator, but rather as a restoration of inner peace to the victim. The implications of this study emphasize the importance of distinguishing forgiveness and reconciliation as two distinct processes, as well as the need for a holistic and contextual approach in assisting victims of domestic violence. In the light of Christian faith, forgiveness is a form of spiritual maturity and the first step toward complete recovery, while reconciliation is only possible if justice, security, and repentance of the perpetrator have been fulfilled.